When Sadness Speaks in Two Tongues: English Code-Switching in Indonesian TikTok Sad Post Captions - Fahri Afandi; Kanaya Nur Nabila; Shalsa Billa Meisya; Rahmadsyah Rangkuti (EXCELLENCE: Journal of English and English Education, 2025)
This study investigates the phenomenon of code-switching in sad post captions on TikTok, focusing on its types, contexts, and communicative functions. Although code switching on digital platforms has been widely studied, the switching context remains underexplored. Using a qualitative descriptive approach with content analysis, this study examines 29 sad-related TikTok captions collected between 2022 and 2025. The analysis is guided by Muysken’s typology, Blom and Gumperz’s contextual categorization, and the functional frameworks of Gumperz and Wardhaugh. The findings show that alternation is the most frequent type of code-switching, indicating frequent shifts between Indonesian and English across clauses. Contextually, metaphorical switching predominates, suggesting that code switching is strongly driven by emotional emphasis. Functionally, message qualification and affective expression dominate, indicating that code switching primarily serves to intensify emotional meaning rather than to convey informational content. This study contributes to sociolinguistics, highlighting how Indonesian bilingual users perform code-switching on TikTok as a strategic medium for emotional expression, identity performance, and digital self-representation.